Orders of the Division of Labor: Self-reference in Organization Structures - Meisinger Norman (Journal of Organizational Sociology)
As a consequence of a variety of dynamics that firms have to deal with, their structures are continually evolving. Some of the resulting patterns and structural properties, however, only become visible at a greater distance from the object of analysis. Thus, this paper analyzes organization structures – conceptualized as the way in which firms divide and institutionalize labor – in their long-term development and shapes the phenomenon of aggregating structural self-reference. This self-reference is decomposed into a taxonomy based on three orders of the division of labor (DoL), each with a corresponding division logic (efficiency, effectivity, and viability) and structural implementation method (specialization, contextualization, and reflection) that firms apply to cope with steadily-changing environmental conditions. Each of the three orders reflects a response to a distinct period of change conceptualized as different bundles of stimuli (the Taylorian, Schumpeterian, and VUCA ‘zeitgeist’) through which new orders of the division of labor emerged.